2017
DOI: 10.1039/c6nr07179a
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of receptor-mediated endocytosis of elastic nanoparticles

Abstract: It is now widely recognized that mechanical properties play critical roles in the cell uptake of nanomaterials. Here we conduct a theoretical study on the kinetics of receptor-mediated endocytosis of elastic nanoparticles that is limited by receptor diffusion, specifically focusing on how the uptake rate depends on the nanoparticle stiffness and size, membrane tension and binding strength between membrane receptors and ligands grafted on the nanoparticle surface. It is shown that, while soft nanoparticles are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
140
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(150 citation statements)
references
References 56 publications
8
140
2
Order By: Relevance
“…Cylindrical NPs and membrane surface tension are not considered. Kinetic reaction between receptor and ligand molecules [32,46,5254], and viscoelastic deformation of cytoskeleton [23,55] are neglected.…”
Section: Resultsmentioning
confidence: 99%
“…Cylindrical NPs and membrane surface tension are not considered. Kinetic reaction between receptor and ligand molecules [32,46,5254], and viscoelastic deformation of cytoskeleton [23,55] are neglected.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, for softer particles, the Design of nanoparticles: A Soft Matter Perspective S Angioletti-Uberti process was frustrated, either due to ligands depletion from the part of the nanoparticle initially not in contact with the cell membrane or because the nanoparticle deformation leads to a metastable wrapped state. All the aforementioned features of soft nanoparticles observed in simulations were either earlier predicted 22 or later rationalised 11,23 by theoretical models. In practice, this was done by starting with the model developed by Gao et al 19 for hard nanoparticles and simply adding an energy term to account for nanoparticles' elastic deformation, further proving the generality of the theoretical model to describe a wide range of nanoparticles' design.…”
Section: Predicting and Controlling Nanoparticles Endocytosismentioning
confidence: 59%
“…Different aspects of receptor-mediated endocytosis have been intensively studied using both theory, 11,[19][20][21][22][23][24][25] and different types of simulations 10,[26][27][28][29][30][31][32][33][34][35][36][37] with coarse-grained models, often combining the two. 10,27 A pioneering work on this problem is that of Gao et al, 19 who proposed a theoretical model to address the size dependence of this process, drawing from previous work on the growth of membrane adhesion patches.…”
Section: Predicting and Controlling Nanoparticles Endocytosismentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the wrapping of harder NMs is kinetically faster than that of soft ones. Moreover, by investigating the correlation between cellular uptake and rigidity of spherical and cylindrical elastic nanoparticles, researchers find that receptor–ligand binding amount (the average binding energy per receptor–ligand bond ranges from 10 k B T to 25 k B T) during the process of endocytosis of elastic nanoparticles is also an important factor to determine the rigidity‐mediated NMs cellular uptake …”
Section: Rigiditymentioning
confidence: 99%